PENGEMBANGAN LKPD BERBASIS PEMBERDAYAAN EKONOMI LOKAL PADA PELAJARAN IPS KELAS VII SMP DI KOTA SINTANG - Suriyanti, Yulia; Relita, Dessy Triana; Thoharudin, Munawar; Sore, Avelius Dominggus (STKIP Persada Khatulistiwa Sintang, 2023)
The success of education, whose main goal is to increase human resources, is influenced by various factors. Factors that influence participation in this success are the teacher's ability to carry out and utilize assessments, evaluation processes and learning outcomes. The development of LKPD is part of printed teaching materials which serve as a guide, complement or means of supporting the implementation of learning plans in the form of worksheets containing material, summaries and instructions for implementing learning tasks that must be carried out by students, including solving and solving activities. problems through experimentation. This research uses research and development methods. This research design uses a 4-D development model, namely defining, designing, developing, disseminating. Research instruments include observation sheets, questionnaires and tests. Analysis of the resulting data is processed using descriptive percentages. From this research, it can be concluded that the LKPD based on Local Economic Empowerment that was developed is suitable for use for social studies learning, namely at SMP Nusantara Indah Sintang, SMP Panca Setya 2 Sintang and SMP Negeri 1 Sintang 86% are in the very appropriate category. The percentage of student responses in the very interested category was 65,71% and teacher responses in the very interested category were 83,33%.